Development of a Mathematical Model for Precise Temperature Measurement in Geoinformation Systems for Monitoring Individual Heat Consumption In Apartment Buildings - Aleksandrovich Larchikov, Andrey; Viktorovich Larchikov, Aleksandr; Borisovich Rygalin, Dmitry (International Journal of Engineering and Technology, 2018)
One of the main energy saving objectives is to find methods for metering individual heat consumption in each apartment of an apartment building. Achievements in the area of microprocessor devices made it possible to create a new type of measurement and control systems for monitoring and metering energy resources. Newly developed heat meters are the ground for fundamental changes in energy saving and energy efficiency. Apartment buildings are heated by various hot water distribution systems, for which it is not always possible to use conventional heat meters. The ambiguity related to the parameters of heat meters can adversely affect the estimation of heat consumption by each apartment in an apartment building. This paper is aimed at analyzing a new contact temperature measurement method and means used to create a system for heat monitoring and metering in an apartment building. The developed system can be used to meter energy resources of facilities distributed in a specific area, with geographic referencing to each facility. This makes it possible to remotely monitor heat energy consumption, which makes the energy consumption control system much more transparent and ensures public control. The system gathers data from a large number of users, processes data in real time and promptly responds to usersâ€™ requests based on recent developments in information technology. An important advantage of the developed system is that it can be used to anticipate emergency situations taking into account various factors, such as weather conditions and the age of buildings. Due to all of the above, the system can be used in the future not only in Russia but also abroad.Â